2001
DOI: 10.1038/sj.cdd.4400799
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation of the bcl-2 family during spermatogenesis: Insights into the sterility of bcl-w−/− male mice

Abstract: Expression of bcl-w, a close relative of bcl-2 is essential for male fertility in mice. Although the initial wave of spermatogenesis in bcl-w 7/7 mice proceeds normally until 3 ± 4 weeks of age, adults fail to produce sperm. To clarify why bcl-w is essential for adult but not juvenile spermatogenesis, we investigated the expression pattern of eight bcl-2 family members. We found that both the level and pattern of expression varied in different cell types during juvenile and adult spermatogenesis. Anti-apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…Partially overlapping Smad6 and Smad7 expression in adult spermatogonia and spermatocytes, and the extension of Smad7 expression into spermatids, further indicates there is precise regulation of TGF␤ signaling inhibition. Hence, transcription of SMAD genes is independently regulated and differs between the first wave of spermatogenesis and the cycling of the adult seminiferous epithelium, a concept we have reported for Bcl2 family members (Meehan et al, 2001). The restricted germ cell production of Smad8 in the adult mouse testis suggests a specific requirement for SMAD8-mediated signal transduction in adult somatic cells and spermatogonia.…”
Section: Discussionmentioning
confidence: 69%
“…Partially overlapping Smad6 and Smad7 expression in adult spermatogonia and spermatocytes, and the extension of Smad7 expression into spermatids, further indicates there is precise regulation of TGF␤ signaling inhibition. Hence, transcription of SMAD genes is independently regulated and differs between the first wave of spermatogenesis and the cycling of the adult seminiferous epithelium, a concept we have reported for Bcl2 family members (Meehan et al, 2001). The restricted germ cell production of Smad8 in the adult mouse testis suggests a specific requirement for SMAD8-mediated signal transduction in adult somatic cells and spermatogonia.…”
Section: Discussionmentioning
confidence: 69%
“…Some proteins of the cellintrinsic pathway, the Bcl-2 family of proteins, are essential for normal spermatogenesis. The expression of Bax, a pro-apoptotic protein, peaks during the time of the massive germ cell death observed at day 22 during postnatal development of the testis in mice (Rodriguez et al, 1997) and is still expressed in pachytene spermatocytes in the adults (Yan et al, 2000;Meehan et al, 2001). In testes of Baxdeficient mice, there was an accumulation of spermatogonia, a phenotype consistent with the failure of germ cell death during the first wave of spermatogenesis (Knudson et al, 1995).…”
Section: Discussionmentioning
confidence: 70%
“…Age dependent changes in cell survival resulting from FSH suppression may be due to developmentally regulated changes in the cellular synthesis of apoptotic regulators, such that documented for members of the Bcl-2 family during the first wave of mouse spermatogenesis (Meehan et al 2001). The Bcl-w (Yan et al 2000) and Bok ) mRNAs were shown to be up-and down-regulated respectively by FSH in vitro, and the bcl-w knockout mouse has elevated germ cell apoptosis following 14 dpp, indicating the potential influence of Bcl-2 family members on the cellular responses in this model.…”
Section: Germ Cell Developmentmentioning
confidence: 99%
“…FSH-regulated apoptosis during the first spermatogenic wave has not been examined, however in adult rats, germ cells are lost through apoptosis (Meachem et al 1999), rather than through reduced proliferation when FSH is manipulated (McLachlan et al 1995). However the regulation of adult spermatogenesis cannot be assumed to be mediated in the same manner as is the first spermatogenic wave, as shifts in the expression patterns of key regulatory genes (i.e., Bcl-2 family members and stem cell factor (SCF) have been observed as Sertoli cells mature and eventually mature germ cell populations emerge (Munsie et al 1997, Huang et al 1992, Meehan et al 2001.…”
Section: Introductionmentioning
confidence: 99%